2019
DOI: 10.1016/j.jhsg.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically Assisted Transosseous Triangular Fibrocartilage Complex Foveal Tear Repair in the United States Military

Abstract: Purpose: To compare subjective and objective midterm functional clinical outcomes of knotless arthroscopic assisted transosseous (AAT) triangular fibrocartilage complex (TFCC) repairs specifically in a cohort of military service members. Methods: Patient charts were reviewed to identify all cases of TFCC repair by a single surgeon from 2012 to 2016. Primary outcome variables were the QuickeDisabilities of the Arm, Shoulder, and Hand score and return to full military duty. Secondary outcome variables were visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…49 Five studies listed DRUJ instability as an exclusion criterion. 27,[37][38][39]44 In Badia and Khanchandani, DRUJ instability was an indication for a different approach of repair than the one studied. 27…”
Section: Journal Of Wrist Surgerymentioning
confidence: 95%
See 4 more Smart Citations
“…49 Five studies listed DRUJ instability as an exclusion criterion. 27,[37][38][39]44 In Badia and Khanchandani, DRUJ instability was an indication for a different approach of repair than the one studied. 27…”
Section: Journal Of Wrist Surgerymentioning
confidence: 95%
“…26,40,48 Fourteen studies reported peripheral TFCC repairs [26][27][28][29][30][31][32][33][34][35][36][37][38][39] and 13 studies reported foveal avulsions of the TFCC. [40][41][42][43][44][45][46][47][48][49][50][51][52] As the pathoanat-omy of these tears and repair techniques differ, the outcomes of peripheral and foveal tears were analyzed separately.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations